Prevalence and Predictors of Domestic Violence among Geriatric Population in a Hilly District of Nepal: A Cross-Sectional Study - Gautam, Sangharsha; Nakarmi, Sumitra; Yadav, Dipendra Kumar (MedS Alliance Journal of Medicine and Medical Sciences, 2021)
INTRODUCTION: Domestic violence has been a challenging issue throughout the globe that leads to the serious health problems and geriatric populations being more vulnerable as they are dependent on family or caregiver. The study aims to identify prevalence of domestic violence and its predictors among geriatric population of Baglung district, Nepal. MATERIALS AND METHODS: A community based cross sectional study was conducted at 2 urban municipalities and 2 rural municipalities of Baglung district, Province number 4, Nepal. A sample of 535 geriatric populations was selected using multi stage cluster sampling. Multivariable logistic regression model was adapted to explore predictors of domestic violence among geriatric population RESULTS: Among 535 geriatric people, the prevalence of domestic violence was 3.5%. Geriatric people belong to dalit ethnicity (aOR=12.7; 95% CI: 2.8-56.3) living with others than spouses (aOR=10.2; 95% CI: 1.2-86.9) and the geriatric who need helper for daily activity (aOR=2.8; 95% CI: 1.0-8.7) were more likely to have experience of DV than their counterparts. CONCLUSIONS: The prevalence of Domestic Violence among geriatric population was very low. However, ethnicity, living other than spouses and assistance needed for daily activities were important predictors of DV among geriatric population. Therefore, Community awareness program regarding consequences of violence targeting elders as well as caregivers could be a public health priority to improve the status of elderly by reducing the elder violence.